Pengenalan Implementasi Modul Tematik dalam Pembelajaran Bahasa Inggris Kelas Dua di Sekolah Dasar - Aulia Agustiani; Hikmah Zalifah Putri; Nurul Masyithah Rery; Herizal (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
This community service program was conducted to introduce and socialize the use of thematic modules in English learning for second-grade students at SD IT Tahfidzul Quran Pekanbaru. The initiative was motivated by challenges in English instruction at Islamic-based elementary schools, where teaching methods remain conventional and teacher-centered, and where there is a lack of contextual materials aligned with students' daily routines and religious values. The thematic module was designed to integrate English vocabulary and structures with familiar themes such as Daily Routines, School Activities, and Family Life, while embedding Islamic values. The program involved three stages: socialization with teachers, classroom simulation with students, and reflective discussion. Results showed that teachers welcomed the thematic approach as more relevant and communicative, while students demonstrated enthusiasm and improved confidence in using English through interactive activities such as role play and storytelling. The program successfully provided alternative teaching media that are contextual, enjoyable, and aligned with the school's vision. It also strengthened collaboration between the university and partner schools in developing innovative English learning practices.